2019
DOI: 10.1590/1980-549720190014.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de anti-hipertensivos e antidiabéticos no Brasil: análise das diferenças socioeconômicas. Pesquisa Nacional de Saúde 2013

Abstract: RESUMO: Objetivos: Avaliar a magnitude de desigualdades socioeconômicas e demográficas da utilização de medicamentos para controle de hipertensão arterial e diabetes mellitus na população brasileira. Método: Foram analisados dados da Pesquisa Nacional de Saúde (PNS) conduzida no Brasil em 2013, com amostra representativa da população com idade de 18 anos ou mais. Foi estimada a utilização de medicamentos para hipertensão e diabetes segundo renda, escolaridade, raça, posse de plano de saúde e região de morad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
2
5
0
11
Order By: Relevance
“…In this study, 90.83% of the respondents did not have private health insurance, indicating that they benefit from public health services, which corroborates other studies on the subject. 1,7,9,11,32,35,37,40,44 Costa et al 11 found that people without private health insurance more frequently use free medication programs, which shows that RFM and SNTP mainly serve those who depend exclusively on government health programs, as was observed in the present study. Moreover, we observed that the medication coverage provided by private insurance was insignificant, as was also reported by Pereira.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, 90.83% of the respondents did not have private health insurance, indicating that they benefit from public health services, which corroborates other studies on the subject. 1,7,9,11,32,35,37,40,44 Costa et al 11 found that people without private health insurance more frequently use free medication programs, which shows that RFM and SNTP mainly serve those who depend exclusively on government health programs, as was observed in the present study. Moreover, we observed that the medication coverage provided by private insurance was insignificant, as was also reported by Pereira.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is clear that Brazilian medication access programs play a fundamental role in minimizing inequality regarding antihypertensive and antidiabetic therapy. 11,38,40 In the present study, most respondents declared themselves to be non-White. Similar racial findings have been observed by other authors, 14,16,27,29 although other national studies 23,25,42,43 have found a majority of Whites in their populations.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Frequências mais reduzidas de tratamento medicamentoso ou a não utilização entre portadores de hipertensão e diabetes, podem estar relacionadas às barreiras no acesso e na adesão ao tratamento, além da possibilidade de alguns segmentos de pacientes estarem reduzindo a utilização de medicamentos e adotando outras formas de controle das doenças, como mudanças de hábitos e de estilos de vida 27 No que se refere ao uso de anti-hipertensivos nas diversas regiões do país, observando-se os anos de 2014 e 2017, destaca-se o aumento da prevalência nas regiões Norte e Nordeste, refletindo possíveis melhorias nas desigualdades regionais. Essas duas macrorregiões, em especial, são menos desenvolvidas social e economicamente, no entanto esses achados podem sugerir avanços na organização das redes que integram o SUS, favorecendo acesso aos serviços em Unidades Básicas de Saúde (UBS), medicamentos e diagnósticos [28][29][30][31] .…”
Section: Discussionunclassified
“…A study conducted with data from the 2011 VIGITEL survey showed a lower prevalence of medication use among diabetic and hypertensive patients, with 78.2% and 72.0%, respectively, compared to the present article 19 . The National Health Survey (2013) showed that 80.2% and 81.4% used drugs to control diabetes and hypertension, respectively 20 . These results suggest a progression in the use of medications for these two chronic conditions.…”
Section: Discussionmentioning
confidence: 99%